Ambient Assisted Living : 7. AAL-Kongress 2014 Berlin, Germany, January 21-22, 2014 - Wichert, Reiner; Klausing, Helmut (Advanced Technologies and Societal Change,, 2015)
In this book, leading authors in the field discuss developments of Ambient Assisted Living. The contributions have been chosen and invited at the 7th AAL congress, Berlin. It presents new technological developments which support the autonomy and independence of individuals with special needs. As the technological innovation raises also social issues, the book addresses micro and macro economical aspects of assistive systems and puts an additional emphasis on the ethical and legal discussion. The presentation is supported by real world examples and applications.